Changing public sector wage differentials in the UK - Richard Disney; Amanda Gosling (Institute for Fiscal Studies (IFS), 2008)
The paper estimates public sector wage differentials and their changes over time for men and women in the United Kingdom using the New Earnings Survey. It presents estimates that are robust to unobserved workforce characteristics and that also show the impact of policy changes and cyclical factors. The methodology also allows us to examine the extent to which discrepancies in public and private sector pay induce changing relative qualities of the sectoral workforces.
Keywords: J31; J58; 330; Public sector; wages; unobservables; Öffentlicher Dienst; Lohndifferenzierung; Schätzung; Großbritannien